Diagnostics of child-parent relations using projective the method «Three trees» - Lupekina, Alena A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is devoted to the problem of diagnostics of child-parent relationship using the projective method «Three trees». The detailed procedure of the method «Three trees». Detailed objectives of the study: establishing object orientation  identification of the child and stage of development of object relations. Specific examples and analyzes the characteristics of drawings.
Keywords: test of «Three trees»; parent-child relations; identification; triangulation